RISK GOVERNANCE AND TRANSBOUNDARY AQUIFERS - Villar, Pilar Carolina (Programa de Pós-Graduação de Geografia Humana e Programa de Pós-Graduação de Geografia Física, 2012)
The international organizations conceive the water crises as a governance matter. Based on this premise and in the risk theory, this paper analyze the meaning of this governance, its relation to the transboundary aquifers risks and the instruments created in the international level to promote groundwater governance. Despite water governance concept has full acceptation, it is still in construction and whose potential to face water risks is ambiguous. The international instruments created to promote transboundary aquifers governance are fragile and need to be legitimated.